The Columbinus Prophecy: Evidence Form Late Medieval Wales. (1st June 2020) - Falileyev, Alexander
The article examines the transmission of the Columbinus prophecy in late medieval Wales. It argues that the Latin next in NLW Peniarth MS 50 is a copy from the lost exemplar on the basis of the analysis of the Welsh translation of the prophecy, the earliest copy of which pre-dates compilation of this codex. The discussion of the extant Welsh and Latin texts known in Britain allows reconstruction of a number of features of the exemplar, and dated it to the 1360s, nearly a century earlier than Peniarth MS 50. This makes the exemplar one of the earliest sources for the circulation of the Latin Prophecy in the British Isles. The paper also considers reasons for the inclusion of the prophecy in late medieval manuscripts in Wales.